Strategic management of disruptive technologies: a practical framework in the context of voice services and of computing towards the cloud. (1st January 2013) - Kopetzky, Roman; Günther, Markus; Kryvinska, Natalia; Mladenow, Andreas; Strauss, Christine; Stummer, Christian
In many industries, large amounts of resources are allocated for continuous technology development. However, these investments may prove inefficient if a disruptive technology arises that provides new and more attractive customer propositions. While this phenomenon has been the subject of numerous papers, there is still a lack of managerial tools that properly address the challenge of responding to this threat. This paper provides an in-depth review of recent developments in the field and, furthermore outlines a tool that supports managers in identifying forthcoming disruptive technologies and providing them with tailored strategic options. The application of this approach is illustrated by means of two case studies: the mass-market voice services and computing organised as a public utility.